2016
DOI: 10.1007/s00449-016-1670-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases immobilization on chitosan-coated magnetic nanoparticles: application for Agave Atrovirens lignocellulosic biomass hydrolysis

Abstract: In the present study, Trichoderma reesei cellulase was covalently immobilized on chitosan-coated magnetic nanoparticles using glutaraldehyde as a coupling agent. The average diameter of magnetic nanoparticles before and after enzyme immobilization was about 8 and 10 nm, respectively. The immobilized enzyme retained about 37 % of its initial activity, and also showed better thermal and storage stability than free enzyme. Immobilized cellulase retained about 80 % of its activity after 15 cycles of carboxymethylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 54 publications
5
43
1
Order By: Relevance
“…Moreover, as an effect of immobilization, thermal vibrations of cellulase biomolecules were reduced, which limited conformational changes caused by heat and helped to maintain the proper globular structure of the entire biomolecule [36,37]. Similar findings to those presented in this study were reported by Sanchez-Ramirez et al, who used another inorganic-organic hybrid support (chitosan-coated magnetic nanoparticles) for covalent immobilization of Trichoderma reesei cellulase, and found that the resulting biocatalytic system exhibited its maximum activity at 60 • C. In addition, after 3 h of incubation at that temperature, it retained about 60% of its initial activity; however, an increase in the temperature by 10 • C caused the relative activity to drop significantly, to below 40% [38]. By contrast, cellulase immobilized on the titania-lignin support retained over 80% of its activity after 3 h of incubation at 70 • C.…”
Section: Stability Study Of Immobilized Cellulasementioning
confidence: 99%
“…Moreover, as an effect of immobilization, thermal vibrations of cellulase biomolecules were reduced, which limited conformational changes caused by heat and helped to maintain the proper globular structure of the entire biomolecule [36,37]. Similar findings to those presented in this study were reported by Sanchez-Ramirez et al, who used another inorganic-organic hybrid support (chitosan-coated magnetic nanoparticles) for covalent immobilization of Trichoderma reesei cellulase, and found that the resulting biocatalytic system exhibited its maximum activity at 60 • C. In addition, after 3 h of incubation at that temperature, it retained about 60% of its initial activity; however, an increase in the temperature by 10 • C caused the relative activity to drop significantly, to below 40% [38]. By contrast, cellulase immobilized on the titania-lignin support retained over 80% of its activity after 3 h of incubation at 70 • C.…”
Section: Stability Study Of Immobilized Cellulasementioning
confidence: 99%
“…Hongdan et al [42] reported that by the longer pretreatment time from 0 to 40 min, the (see Figure 7). The maximum sugar yield was obtained at early 8 h of hydrolysis time and then decreased/ tended to be constant exceed 8 h. The phenomenon was confirmed by Sanchez-Ramirez [46]. They showed that the enzyme activity decreased continually at 60 °C incubation after 6 h of enzymatic hydrolysis.…”
Section: Scw Effect Towards Enzymatic Hydrolysis Performancementioning
confidence: 57%
“…These values represent a 3.3-fold decrease in Ea for immobilized xylanase and a 1.9-fold decrease for immobilized FPase relative to the free enzymes. The changes observed at acidic pH values ( Figure 1) may be explained by the ionic interactions between the enzyme and the support's surface [26]. In addition, internal pH gradients may be formed in enzymes immobilized on porous supports due to diffusion limitations of both substrate and product, resulting in pH changes away from the optimal found in the bulk [9].…”
Section: Effect Of Ph and Temperature On Xylanase And Filter Paper-asmentioning
confidence: 99%
“…The temperature dependence of the catalytic reaction rate observed through the Arrhenius equation evidences the improvement that immobilization can produce in enzymes' conformational changes as reported by [12,27,28], thus, the immobilized enzymes were able to catalyze the hydrolysis of substrates with a lower Ea when compared to free enzymes. The changes observed at acidic pH values (Figure 1) may be explained by the ionic interactions between the enzyme and the support's surface [26]. In addition, internal pH gradients may be formed in enzymes immobilized on porous supports due to diffusion limitations of both substrate and product, resulting in pH changes away from the optimal found in the bulk [9].…”
Section: Effect Of Ph and Temperature On Xylanase And Filter Paper-asmentioning
confidence: 99%